Persuasive artistry : studies in New Testament : rhetoric in honor of George A. Kennedy - Watson, Duane F.; Kennedy, George Alexander (JSOT Press, 1991)
Crossing diverse strains of plants often yields a hybrid more vibrant than the parent strains. The same can be said of crossing diverse branches of knowledge, as in the integration of biblical and rhetorical studies that has produced the new hybrid of interpretative rhetorical criticism. This integration is due in no small measure to the creative efforts of George A. Kennedy. In this well-integrated volume of essays in his honour, 17 scholars display the influence of the approach taken by Kennedy and others upon the interpretation of the Gospels, Acts, Romans, 2 Corinthians, Galatians, and Ephesians.